2016
DOI: 10.1109/lmwc.2016.2615358
|View full text |Cite
|
Sign up to set email alerts
|

Auto-Tuning and Self-Calibration of High-Sensitivity Radio Frequency Interferometers

Abstract: We demonstrate a technique that automatically tunes the sensitivity of a radio-frequency (RF) interferometer with a tunable liquid attenuator by accurately changing its liquid volume. The obtained effective quality factor (QEFF) of the interferometer is up to 1×108 at ~5 GHz. The QEFF is ~100 times higher than previously reported results. When material-under-test (MUT), i.e., methanol-water solution in this work, is used for the tuning, a self-calibration and measurement process is demonstrated from 2 GHz to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Figure 5 shows the antennas' directivities. Equation (5) gives the space-time applied at the add port and equations (6 and 7) give the microring output at throughput and drop ports. The output at the throughput and drop ports are normalized using equations (8 and 9).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows the antennas' directivities. Equation (5) gives the space-time applied at the add port and equations (6 and 7) give the microring output at throughput and drop ports. The output at the throughput and drop ports are normalized using equations (8 and 9).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…An interferometer is an optical device which is employed as sensors for many physical quantities. An interferometer has different configurations which are employed for sensing applications [1][2][3][4][5][6][7][8]. The Sagnac interferometer is one of the configurations of an interferometer which is the focus of this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow cell forms the sample-under-test (SUT) branch while the tuning branch has a digital tunable attenuator (DTA) and a phase shifter. The basic MIM working principle is described in previous work. The introduction of DTA and computer control are essential for the proposed HPLC measurements.…”
Section: Design Considerationmentioning
confidence: 99%
“…In this work, we propose and demonstrate a microwave flow detector technique that is promising to address the RI detector difficulties discussed above. The detector is based on our previous work on microwave interferometers (MIMs). In this study, an electronically tunable MIM is developed and demonstrated for HPLC measurements under isocratic and gradient elution operations. We also show the quantification of coeluted vitamin E succinate (VES) and vitamin D3 (VD3).…”
mentioning
confidence: 99%